Religion - Thompson, Ian, 1955- (London: Longman, 1986)
Identifies the themes, issues, and trends of religion and discusses the relationship between sociology and religion.
Includes index.
Includes bibliography: p. 101-103.
Keywords: Religion and sociology; Religion; Religion and sociology